Self‐Reported Physical Function As a Predictor of Hospitalization in the Lifestyle Interventions and Independence for Elders Study. Issue 10 (3rd October 2018) - Callahan, Kathryn E.; Lovato, Laura; Miller, Michael E.; Marsh, Anthony P.; Fielding, Roger A.; Gill, Thomas M.; Groessl, Erik J.; Guralnik, Jack; King, Abby C.; Kritchevsky, Stephen B.; McDermott, Mary M.; Manini, Todd; et al.
Abstract : Objectives: To explore whether baseline scores on the Mobility Assessment Tool—short form (MAT‐sf), a brief, animated, computer‐based means of assessing mobility that predicts mobility disability, are associated with number of hospitalizations and time to first hospitalization over a median follow‐up of 2.7 years. Design: Post hoc analysis of prospectively gathered data from the Lifestyle Interventions and Independence for Elders (LIFE) Study, a randomized clinical trial of lifestyle interventions to preserve mobility in older adults. Setting: Eight U.S. academic medical centers. Participants: Of 1, 635 sedentary community‐dwelling older adults enrolled in LIFE, 1, 574 completed baseline physical function screening including the MAT‐sf, with baseline scores ranging from 30.2 (low function) to 69.8 (high function) on a scale from 30 to 80. Measurements: Number of hospitalizations and time to first hospitalization, adjusted for age, sex, race, living alone, clinical site, baseline comorbidities, number of prescription medications, and cognition. Results: Of the 1, 557 participants with data regarding hospitalization status, 726 (47%) had at least 1 hospitalization; 78% of these had 1 or 2 hospitalizations. For every 10‐point lower MAT‐sf score, the rate of all hospitalizations was 19% higher in those with lower scores (adjusted rate ratio=1.20, 95% confidence interval (CI)=1.08–1.32, p<.001). Lower baseline MAT‐sf scores were also associated with greater risk of first hospitalization (adjusted hazard ratio=1.20, 95% CI=1.09–1.32, p<.01, per 10‐point lower MAT‐sf score). Conclusion: Low MAT‐sf scores identify older adults at risk of hospitalization; further study is needed to test interventions to reduce hospitalizations in these individuals.